Series Solution Of A Three Species Food Chain Model Using Adomian Decomposition Method(ADM) - Roy, Prodip; Pramanik, Sanjukta; Sarkar(Mondal), Seema; Biswas, Swagata; Das, Krishna Pada (Journal of Applied Nonlinear Dynamics, 2026)
The solution of a set of non-linear differential equations applying Adomian Decomposition Method (ADM) provides fast computation for the solution. The main part of this method is calculating Adomian polynomials with respect to nonlinear terms. Here, we analyze an ecosystem with one prey and two predator species. The functional response among the species is taken as ratio dependent. We have discussed local stability analysis of our proposed model around different equilibrium points. We have found out the approximate series solution of our proposed system using Adomian decomposition method. We have presented some graphical examples to show the ability of ADM for a nonlinear set of differential equations.